Uji Beberapa Konsentrasi Cendawan Entomopatogen Beauveria bassiana Vuill Lokal dan Cordyceps militaris (L:Fr) Lokal Terhadap Hama Ulat Api Setothosea asigna Van Eecke pada Tanaman Kelapa Sawit - Nurjayanti Nurjayanti; Desita Salbiah; Agus Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Setothosea asigna is a major pest that requires attention to oil palm plantations. One effort to do pest control  S. asigna is to use entomopathogenic fungi. The entomopathogenic fungi have the prospect to be developed because it is safe for the environment and available in nature. The objectives of this research were to obtain a better concentration of entomopathogenic fungi local B. bassiana and local C. militaris to control nettle caterpillar S. asigna at oil palm plantations. The experiment arranged in Complete Randomized Design. Research carried out experiments of  7 treatment with 4 replication so that obtainable 28 unit trial. The treatments were without entomopathogenic fungi 0 g/l of water, B. bassiana 25 g/l of water, B. bassiana 50 g/l of water, B. bassiana 75 g/l of water, C. militaris 25 g/l of water, C. militaris 50 g/l of water, C. militaris 75 g/l of water. The results showed that entomopathogenic fungi local C. militaris is better used to control nettle caterpillar pests S. asigna compared with entomopathogenic fungi local B. bassiana. Concentration of  local C. militaris 25 g/l of water with conidia density 58.5 x 107 kon/ml is capable of causing a early death nettle caterpillar S. asigna 24 hours after application, lethal time 50 is 94.50 hours after application and 82.50% total mortality. Keyword: Nettle caterpillar Setothosea asigna van Eecke, entomopathogenic fungi local, Beauveria bassiana Vuill and Cordyceps militaris (L:Fr).